Evaluation of experimentally obtained permeance based on module simulation: How should permeance be evaluated?. Issue 7 (6th May 2020) - Moriyama, Norihiro; Haraya, Kenji; Nagasawa, Hiroki; Kanezashi, Masakoto; Tsuru, Toshinori
Abstract: Permeance and permeance ratio in binary separation generally are obtained from experimental data using an analytical permeance equation consisting of the logarithmic average of the partial pressure difference (hereafter, approximate permeance equation). The aim of the present study was to clarify the applicable range for this equation. First, the separation performance of a membrane module was calculated with various given membrane properties (permeance, permeance ratio) and operation conditions (pressure, flow rate) via numerical computation. The obtained concentrations and flow rates in the retentate and permeate were used to calculate permeances via approximate permeance equation, and the validity was discussed by comparing permeances used for numerical computation with obtained ones. The present work clarifies the validity of the approximate permeance equation, and yields a general guideline stipulating that the partial pressure difference across the membrane at the inlet and outlet should maintain more than 60% to obtain the correct permeance. Abstract :